Przegroda chórowa i lektorium w kościele Trójcy Świętej w Krakowie rekonstrukcja - datowanie - użytkowanie = Chancel screen in the Church of the Holy Trinity in Cracow : reconstruction, dating, use - Szyma, Marcin; Bojęś-Białasik, Anna; Czechowicz, Jacek; Czyżewski, Krzysztof J. 1963-; Walczak, Marek 1965- (2021)
An attempt to reconstruct the rood screen from the mid-13th century and of the chancel screen from the late 14th century in Cracow's Dominican Church is presented; the reconstruction is based on excavations, architectural research, written records, and laser scanning measurements of the Church. The first screen was a partition wall opened up with two passages. The second, of the type of a Hallenlettner type was five-span with the lateral spans functioning as separate chapels and the middle span communicating the nave with the gallery. In 1543, the chancel screen was altered owing to the construction of the Chapel of St Hyacinth on the first storey. In 1581-1583, the chancel screen was pulled down as the Chapel was extended.